2015
DOI: 10.1097/md.0000000000001941
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Evaluation Tool (ET-CET) Indicates Increase of Diagnostic Skills From Small Bowel Capsule Endoscopy Training Courses

Abstract: Small bowel capsule endoscopy (SBCE) has become a first line diagnostic tool. Several training courses with a similar format have been established in Europe; however, data on learning curve and training in SBCE remain sparse.Between 2008 and 2011, different basic SBCE training courses were organized internationally in UK (n = 2), Italy (n = 2), Germany (n = 2), Finland (n = 1), and nationally in Germany (n = 10), applying similar 8-hour curricula with 50% lectures and 50% hands-on training. The Given PillCam S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
(22 reference statements)
1
21
0
Order By: Relevance
“…Evaluation of hands-on CE training has shown an improvement in diagnostic accuracy but does not define competence and readiness for independent practice. 27,28 There remains ambiguity on the optimal assessment method for competence. Read et al 29 distributed an email survey to gastroenterology fellowship program directors in the United States (59 program directors responded, which was a 35.1% response rate) that indicated most gastroenterology programs (84.8%) required trainees to complete CE training during their fellowship.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of hands-on CE training has shown an improvement in diagnostic accuracy but does not define competence and readiness for independent practice. 27,28 There remains ambiguity on the optimal assessment method for competence. Read et al 29 distributed an email survey to gastroenterology fellowship program directors in the United States (59 program directors responded, which was a 35.1% response rate) that indicated most gastroenterology programs (84.8%) required trainees to complete CE training during their fellowship.…”
Section: Discussionmentioning
confidence: 99%
“…Albert et al[32] developed an evaluation tool (ET-CET) to assess the impact of hands-on capsule endoscopy training on the diagnostic accuracy of the examination. ET-CET consists of 10 capsule endoscopy videoclips.…”
Section: Evaluation Testsmentioning
confidence: 99%
“…Numerous studies have compared CE reading between experts, novices and nurses (59)(60)(61). Whilst some level of prior conventional endoscopy experience is probably helpful for novice CE readers in training (59,62), a high level of experience does not seem to add further benefit (63). Nurses are as capable of reading and recognising CE abnormalities as doctors: whilst they may identify additional insignificant findings, no serious pathology is missed compared to expert physicians (60,61,64).…”
Section: Reading and Reporting Ce Videosmentioning
confidence: 99%
“…There are currently several CE training courses established in Europe. A simple evaluation tool (ET-CET) based on interpretation of video clips was carried out to identify factors related to the learning curve of CE among trainees, nurses and doctors attending courses offering a common core curriculum (62). The study found that previous CE experience was associated with higher baseline scores (before the course) for correct diagnosis.…”
Section: Reading and Reporting Ce Videosmentioning
confidence: 99%